Characteristics of Aerosol WSI With High‐Time‐Resolution Observation Over Arctic Ocean. Issue 9 (28th August 2020) - Yu, Congcong; Yan, Jinpei; Zhang, Honghai; Lin, Qi; Zheng, Hongguo; Zhong, Xinlin; Zhao, Suli; Zhang, Miming; Zhao, Shuhui; Li, Xiaojun
Abstract: In the current study, the characteristics of aerosol water‐soluble ions (WSI) were investigated via high‐time‐resolution observations as part of the nineth Chinese National Arctic Research Expedition (CHINARE) in 2018. WSI, including Cl −, SO4 2−, NO3 −, NO2 −, F −, Br −, Na +, NH4 +, K +, Ca 2+, Mg 2+, and Methanesulfonic acid (MSA − ), were measured using an online ion chromatography system deployed on the Xuelong research vessel. Moreover, aerosol particle sources were analyzed in order to clarify the impacts of marine emissions and anthropogenic sources on atmospheric aerosols in the Arctic Ocean. Sea salt ions (Na + and Cl − ) were observed to be the most dominant compounds, accounting for 53.5% of the total WSI, followed by the secondary ions (SO4 2−, NH4 +, and NO3 − ), which accounted for 36.0%. Furthermore, similar spatial distributions of MSA − and SO4 2− were observed during the measurement period. High levels of Na + were observed in the areas close to the land and Central Arctic Ocean, attributed to wind speed. In the open ocean, NH4 + and NO3 − concentrations were extremely low, however, high levels of NH4 + and NO3 − were observed in the coastal area close to Alaska and Russia. This indicates that these aerosol particles were influenced by the anthropogenic sources in these regions. In addition, mean fluxes of NO3 − and NH4 + were determined as 42 ± 41 and 347 ± 166 μg m −2  day −1 in the Arctic Ocean, respectively. Key Points: Two high level regions of sea salt aerosol and three high level regions of sulfur‐containing aerosol were observed over Arctic Ocean (AO) Sea salt ions were the most dominant compounds, accounting for 53.5% of WSI, followed by the secondary ions, which accounted for 36.0% NH4 + and NO3 − concentrations were extremely low in the open AO but high in coastal regions due to the influence from anthropogenic sources